1983
DOI: 10.1002/ana.410140402
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding brain capillary function

Abstract: The endothelial cells in brain capillaries form a blood-brain barrier which limits and controls the movement of solutes between blood and brain. These cells contain continuous tight junctions and exhibit a low rate of pinocytosis, resulting in formation of a permeability barrier to macromolecules and many polar compounds. However, brain capillary endothelial cells also contain specialized transport systems that facilitate blood-to-brain transfer of some solutes and actively pump other solutes from brian to blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1984
1984
1998
1998

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(31 citation statements)
references
References 69 publications
0
30
0
1
Order By: Relevance
“…1, inset). Goldstein and Betz (1983)]. The ac tive extrusion of K + from the brain to the blood and the corresponding entry of Na + from blood to brain are thought to be regulated , at least in part , by the membrane-bound enzyme Na + , K + -ATPase.…”
Section: Resultsmentioning
confidence: 99%
“…1, inset). Goldstein and Betz (1983)]. The ac tive extrusion of K + from the brain to the blood and the corresponding entry of Na + from blood to brain are thought to be regulated , at least in part , by the membrane-bound enzyme Na + , K + -ATPase.…”
Section: Resultsmentioning
confidence: 99%
“…This is unlikely because there seem to be no functional or morphological differences between capillaries in different cortical layers, 54 - 55 and studies assessing capillary plugging histologically (see above) found no preferential distribution regarding the cortical layers.…”
Section: Does Leukocyte Flogging Cause Postischemic Cortical Hypoperfmentioning
confidence: 96%
“…The brain endothelium is a dynamic interface that functions as a potentially immunoreactive surface for the modulation of immune and inflammatory responses (27,28). Endothelial cells form an integral part of the blood-brain barrier (BBB), a selectively permeable transport barrier for substance exchange across capillary walls (29,30). Infection of human brain capillary endothelial (HBCE) cells may alter the immunoreactivity of the endothelium or compromise the integrity of the BBB.…”
Section: For a Review) Human Immunodeficiency Virus (Hiv) Hasmentioning
confidence: 99%